Investigation of genetic factors regulating chlorophyll and carotenoid biosynthesis in red pepper fruit - Jang, Siyoung; Kim, Geon Woo; Han, Koeun; Kim, Young Min; Jo, Jinkwan; Lee, Seo-Young; Kwon, Jin-Kyung; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2022)
Chlorophylls and carotenoids are synthesized in chloroplast and chromoplast, respectively. Even though two pigments are generated from the same precursor, the genetic correlation between chlorophyll and carotenoid biosynthesis has not been fully understood. We investigated the genetic correlation of chlorophyll and carotenoid biosynthesis during fruit ripening. Two RIL populations, LA RILs derived from a cross between C. annuum ‘Long Sweet’ with light-green and light-red fruit and C. annuum ‘AC2212’ with dark-green and brown-fruit and FC RILs from C. annuum ‘3501’ with dark-green and dark-red fruit and C. annuum ‘3509’ with intermediate green and light-red fruit, were used. As the fruit ripened, three accessions produced high levels of xanthophyll. The dark-green immature fruit accumulated more total carotenoids than the light-green fruit. This trend corresponded to the expression pattern of 1-deoxy-d-xylulose 5-phosphate synthase (DXS) and CaGLK2 genes during fruit development. The expression levels of DXS and CaGLK2 in the dark-green accession ‘3501’ were significantly higher than those of ‘3509’ and ‘Long Sweet’ at the early stages of fruit development. Furthermore, the genotype analysis of the transcription factor controlling chloroplast development (CaGLK2) in LA RILs revealed that CaGLK2 expression affected both carotenoid and chlorophyll contents. The SNP linkage maps were constructed using genotyping-by-sequencing (GBS) for the two populations, and QTL analysis for green fruit color intensity and carotenoid content was performed. The QTL (LA_BG-CST10) for capsanthin content in LA RILs located at 24.4 to 100.4 Mbp on chromosome 10 was overlapped with the QTL (FC15-Cap10) for capsanthin content in FC RILs. Three QTLs for capsanthin content, ASTA value, and immature green fruit color intensity were also overlapped at 178.2 to 204 Mbp on chromosome 10. At 151.6 to 165 Mbp on chromosome 8, QTLs (FC15-tcar8, FC17-ASTA8.1, and FC17-ASTA8.2) for total carotenoid content and ASTA value were discovered, and this region contained 2-C-methyl-d-erythritol 4-phosphate cytidylyltransferase (MCT), which is involved in the MEP pathway. This result is the first report to show the correlation between carotenoid and chlorophyll biosynthesis in pepper. This research will expand our understanding the mechanism of the chloroplast-to-chromoplast transition and the development of high pigment pepper varieties.